BAT ALGORITHM IMPLEMENTATION TO OPTIMALLY DESIGN THE STABILIZER POWER SYSTEM ON THE SUPPA GENERATOR - Muhammad Ruswandi Djalal; Herman HR (SINERGI, 2019)
One of the control devices that can be used to strengthen the performance of PLTU Suppa is the installation of Power System Stabilizer. The problem of using Power System Stabilizer (PSS) in generator excitation is how to determine the optimal PSS parameter. To overcome these problems, the authors use a method of intelligent bats to design PSS. Bat's algorithm will work based on the specified destination function, which is an Integral Time Absolute Error (ITAE). In this research, we will see the deviation response of velocity and the rotor angle of the suppa generator in case of interference. The results of the analysis show that the uncontrolled system produces oscillation overshoot speed of -0.02437 pu to 0.006517 pu, conventional PSS about -0.02186 pu to 0.004623 pu and with PSS Bat overshoot of -0.01507 pu up to 0.0006223 pu. A loop for rotor angle response shows good results with reduced oscillation and rapidly leading to steady-state conditions. From the analysis results can be concluded, the performance of suppa generator is increased with the installation of Power System Stabilizer with optimal PSS parameters, with parameters respectively Kpss = 32.2077, T1 = 0.0173, T2 = 0.0401, T3 = 0.9174, T4 = 1.2575.